ZAKAT SEBAGAI IBADAH MALIYAH IJTIMA’IYAH DALAM PERSPEKTIF ILMU EKONOMI ISLAM - WIDI NOPIARDO (JURIS (Jurnal Ilmiah Syariah), 2016)
Zakat is a part of the discussion of Islamic economics. In the perspective of Islamic economics zakat has a very important role. Zakat has a strategic role in the fight against poverty or economic development. Zakat has an enormous influence in many respects human life, among which is the effect on the economy. Zakat is a tool that can be used to stabilize the economic life, zakat can strengthen economic solidarity among members of society, and ultimately will create economic stability. In addition to containing the values of worship, zakat also contains socio-economic value to people's lives.Kata kunci: zakat, perspektif, dan ilmu ekonomi Islam